Neurogenic Pulmonary Edema Associated with Underlying Lung Disease after a Breakthrough Seizure - Gaurav Dutta; Spiro Demetis (Case Reports in Medicine)
Neurogenic pulmonary edema (NPE) can result from various central nervous system disorders such as brain malignancies, traumatic brain injuries, infections, and seizures. Although the pathogenesis is not completely understood, NPE creates an increase in pulmonary interstitial and alveolar fluid. It has been reported with prolonged seizure activity. Treatment for NPE is largely supportive. If unrecognized, it can lead to hypoxia and respiratory arrest. We report a case of NPE in a middle-aged female patient following a breakthrough seizure in whom an immunological cause for respiratory findings was high on the differential list, based on her past medical history and chronicity of symptoms. Rapid symptomatic and radiological improvement following hospitalization led to the correct diagnosis.